2018
DOI: 10.1016/j.ymgme.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease revisited: Management and treatment recommendations for adult patients

Abstract: Fabry disease is an X-linked lysosomal storage disorder caused by mutations in the GLA gene leading to deficient α-galactosidase A activity, glycosphingolipid accumulation, and life-threatening complications. Phenotypes vary from the "classic" phenotype, with pediatric onset and multi-organ involvement, to later-onset, a predominantly cardiac phenotype. Manifestations are diverse in female patients in part due to variations in residual enzyme activity and X chromosome inactivation patterns. Enzyme replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
557
0
63

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 485 publications
(626 citation statements)
references
References 93 publications
6
557
0
63
Order By: Relevance
“…In general, existing guidelines recommend ERT initiation for all patients at the time of symptom onset 35,36 or organ involvement. 37,78 However, opinion diverges regarding the age of ERT initiation in asymptomatic boys, with recommendations ranging from 8-10 years in the 2016 US guidelines 38 to 10-13 years in the 2006 international guidelines 32 to 16 years in the 2015 European guidelines. 34 During the shortage of agalsidase beta, a European group of experts recommended prioritisation of children for treatment allocation.…”
Section: Treating Organ Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, existing guidelines recommend ERT initiation for all patients at the time of symptom onset 35,36 or organ involvement. 37,78 However, opinion diverges regarding the age of ERT initiation in asymptomatic boys, with recommendations ranging from 8-10 years in the 2016 US guidelines 38 to 10-13 years in the 2006 international guidelines 32 to 16 years in the 2015 European guidelines. 34 During the shortage of agalsidase beta, a European group of experts recommended prioritisation of children for treatment allocation.…”
Section: Treating Organ Involvementmentioning
confidence: 99%
“…GI involvement is common in children with FD and includes nausea, vomiting, non-specific abdominal pain, constipation, diarrhoea. It is now understood that FD morbidity starts in childhood and worsens with age, and that some girls can have severe disease due to skewed XCI.Numerous studies suggest that early initiation of ERT, even before symptoms appear, can protect organs from damage in later life.In general, existing guidelines recommend ERT initiation for all patients at the time of symptom onset35,36 or organ involvement 37,78. Eating small, frequent meals and dietary restrictions can also help 35.…”
mentioning
confidence: 99%
“…В настоящее время разработана генотип-специ-фическая терапия болезни Фабри, направленная на замещение фермента. Фермент-заместительная терапия назначена пациентке на основании послед-них международных рекомендаций [5].…”
Section: кардиологический фенотип болезни фабриunclassified
“…It may occur in different scenarios in the various forms of disease presentation. It may be part of a multisystem disorder in the context of the classic (early-onset) phenotype of the disease, 14 or the heart may be the only affected organ with scarce or no extracardiac involvement (cardiac variant or late-onset variant of FD). 15 Studies have shown that symptoms resulting from cardiac involvement occur in 40%-60% of patients with FD, and although cardiac involvement usually begins in the early stages of life, clinical manifestations appear at about 32 years of age in men and 40 years of age in women.…”
Section: Introductionmentioning
confidence: 99%